MODERASI CORPORATE SOCIAL RESPONSIBILITY DALAM PENGHINDARAN PAJAK DAN TATA KELOLA PERUSAHAAN TERHADAP MANAJEMEN LABA - Ramadana, Mariska; Irawan, Helen; Butar-Butar, Dea Tiara Monalisa (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
Earnings management practices have an impact on the quality of financial reports which can influence investor decisions and company reputation. This research aims to investigate the moderating role of CSR on the relationship between tax avoidance and corporate governance on earnings management practices. As many as 197 samples from 49 companies listed on the Indonesia Stock Exchange during 2018-2022 were analyzed using multiple linear regression. The research results show that tax avoidance and female commissioners have a significant negative effect on earnings management, while independent commissioners and audit quality have a significant positive effect on earnings management. CSR positively moderates the influence of female commissioners on earnings management, but negatively moderates audit quality on earnings management. This research implies that the structure and composition of the board of commissioners, including the presence of female commissioners, can play an important role in managing earnings management, while audit quality is highly dependent on the implementation of strict audit standards.